About the Saker Falcon Situation in the Southern Balkhash Region in the South-East of Kazakhstan - Altai Zh. Zhatkanbaev; Sergey S. Shmygalev; Nurlan M. Dosov; Aleksey A. Grachev; Ermek S. Musyrpanov (Пернатые хищники и их охрана)
The Saker Falcon (Falco cherrug) has been a breeding and wintering species in the southern shore of Lake Balkhash region for the last two decades. There is a publication describing the first known case of the Saker Falcon nesting there in 2013 and the wintering of a pair in the transition landscape of wetland to desert biome landscape of this geographical area (Zhatkanbaev, 2014). By the end of 2017, the nesting population of the species numbered at least 20 pairs.